2001
DOI: 10.1021/bi001659k
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin−Proteasome Pathway Plays an Essential Role in Proteolysis during Trypanosoma cruzi Remodeling

Abstract: Here, we document for the first time the presence of the 26S proteasome and the ubiquitin pathway in a protozoan parasite that is in an early branch in the eukaryotic lineage. The 26S proteasome of Trypanosoma cruzi epimastigotes was identified as a high molecular weight complex (1400 kDa) with an ATP-dependent chymotrypsin-like activity against the substrate Suc-LLVY-Amc. This activity was inhibited by proteasome inhibitors and showed same electrophorectic migration pattern as yeast 26S proteasome in nondenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 53 publications
3
66
0
2
Order By: Relevance
“…The subsequent morphological changes involving thickening of the posterior end and progressive shortening of the parasite around itself in a helical fashion, along with a gradual internalization of the flagellum resemble the changes for tissue-culture-derived trypomastigotes as described above. The fact that early and late morphological changes are associated with the different environmental conditions surrounding extracelullar primary amastigogenesis may provide an opportunity to study the role of ubiquitin (UB)-proteosome system, which was recently shown to be involved in the remodeling process of trypomastigote transformation (De Diego et al 2001). It is worth noting that the early events described during primary amastigogenesis were not observed when tissueculture derived trypomastigotes transformed into amastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent morphological changes involving thickening of the posterior end and progressive shortening of the parasite around itself in a helical fashion, along with a gradual internalization of the flagellum resemble the changes for tissue-culture-derived trypomastigotes as described above. The fact that early and late morphological changes are associated with the different environmental conditions surrounding extracelullar primary amastigogenesis may provide an opportunity to study the role of ubiquitin (UB)-proteosome system, which was recently shown to be involved in the remodeling process of trypomastigote transformation (De Diego et al 2001). It is worth noting that the early events described during primary amastigogenesis were not observed when tissueculture derived trypomastigotes transformed into amastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…Proteasomes are large, non-lysosomal, multi-subunit protease complexes. They are characterised by evolutionarily conserved proteins and are present in Trypanosoma brucei [8], Trypanosoma cruzi [9], Toxoplasma gondii [10], Plasmodium spp. [11], Entamoeba histolytica and Entamoeba invadens [12], as well as in Leishmania mexicana [13].…”
Section: Introductionmentioning
confidence: 99%
“…De Diego et al (2001) assumed that the enzyme plays an important role during the remodeling phase of Trypanosoma cruzi and indicated a significant role of the proteasome during the development of organisms. In the arthropod Drosophila melanogaster, a cell-specific accumulation of proteasome was reported during the early development (Klein et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…We assume that this mechanism, as it represents a period of enhanced protein turnover, will strongly depend on the balanced interplay of proteasomal activities. The proteasome is one of the main regulators of the cell-cycle (Richter-Ruoff and Wolf 1993;Naujokat and Hoffmann 2002), differentiation processes such as remodeling (De Diego et al 2001) and growth. Therefore, it seems likely that especially in the developmental stages which are characterized by high mitotic activity, growth and high transcription rates might demand an active and regulating proteasome.…”
Section: Discussionmentioning
confidence: 99%